Corporate Strategy of PT Miga Orricom Indonesia - Hidayat, Teddy Mulyadi; Wandebori, Harimukti (The Indonesian Journal of Business Administration, 2013)
PT. Miga Orricom Indonesia is a supply company for electrical measurement devices and wireless products. After grow up in the last 10 years, the company’s achievement was declined. Based on change in PLN market in 2011, the opportunity exists is becoming a threat for the company. After the e-procurement, the company lost the market significant The total sales fell to the lowest level in the last five years and net profit margin declined from 9.3% to 3.5%. However, there are no strategic plans which can minimize the threat and enhancing the opportunity exist, yet. So, the fundamental issue nowadays is how the company minimizing the strategic gap exists in between what the company offers and the market needs. The business issue has been explored by Strategic Management Model.  As a result, strategic policy of the company to develop a product portfolio of services with YANTI brand in PLN DJBB has been implemented in first year. Dashboard monitoring program has been developed in accordance with the new corporate strategic planning.         Key Words : corporate strategy, differentiation focus, forward horizontal integration